2023
DOI: 10.3390/microbiolres14010006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Stratification of COVID-19 Infections Using Differential Plasma Levels of D-Dimer: A Two-Center Study from Saudi Arabia

Abstract: Background: D-dimer, generated upon the degradation of fibrin, is extensively used to detect thrombosis in various diseases. It is also explored as a marker for thrombosis in cases with COVID-19 disease. Few studies have confirmed its utility as a marker for assessing disease severity. Objectives: The current research was undertaken to determine the role of D-dimer in patients with COVID-19 and to investigate any association with the progression and severity of the disease in the Saudi population. Methods: Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…An increased correlation between the severity and outcome of COVID-19 with increased levels of DD was reported. [ 17 , 18 ] Baroiu et al [ 19 ] , 2022 reported a strong correlation between DD and COVID-19 severity. Hui Long et al [ 20 ] , 2020 investigated the role of coagulation indicators like DD, PT, and PTT, in predicting the severity and prognosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…An increased correlation between the severity and outcome of COVID-19 with increased levels of DD was reported. [ 17 , 18 ] Baroiu et al [ 19 ] , 2022 reported a strong correlation between DD and COVID-19 severity. Hui Long et al [ 20 ] , 2020 investigated the role of coagulation indicators like DD, PT, and PTT, in predicting the severity and prognosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Fever, cough, dyspnea, wheezing, and excessive mucus production were the most prevalent symptoms of COVID-19 disease [ 5 ]. Death in severe COVID-19 infection is generally caused by the development of ARDS, sepsis, and multiple organ failure, all of which are a result of dysfunctional immunological, endothelial, and coagulation responses characterized by thrombocytopenia, leukopenia, hypercoagulation, and elevated D-dimer levels [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the disease caused by SARS-CoV-2 was addressed by Alsrhani and colleagues [ 2 ]. In their work, these authors addressed the role played by D-dimer in patients with COVID-19, and investigated its association with the progression and severity of the disease in a study involving two Saudi medical centers [ 2 ].…”
mentioning
confidence: 99%
“…The severity of the disease caused by SARS-CoV-2 was addressed by Alsrhani and colleagues [ 2 ]. In their work, these authors addressed the role played by D-dimer in patients with COVID-19, and investigated its association with the progression and severity of the disease in a study involving two Saudi medical centers [ 2 ]. The authors quantified plasma D-dimer levels in the samples collected from 148 COVID-19 patients, and found that the plasma D-dimer concentrations were significantly elevated in COVID-19 patients compared to normal, uninfected controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation